Traditional Herbal Practices as Economic Drivers: Educational Institutions and the Knowledge Society in Assam - Hazarika, Lima; Mahanta, Bidisha (South Eastern European Journal of Public Health, 2025)
The essence of Assam lies in its stunning landscapes and rich cultural diversity. This Northeast Indian state is a vibrant melting pot of ethnicities, each weaving a distinct thread into its unique socio-cultural fabric. The Deori and Sonowal Kachari tribes of Assam have long relied on traditional herbal practices for healthcare, spiritual rituals, and economic sustenance. These communities possess invaluable indigenous knowledge passed down through generations, forming an integral part of Assam’s cultural heritage. However, the potential of this herbal knowledge remains largely untapped in the broader economic and scientific landscape. This paper explores how traditional herbal practices can serve as economic drivers by integrating them with scientific research and market mechanisms. The role of educational institutions in bridging the gap between traditional practices and modern economies is examined, focusing on how universities and research centers can facilitate knowledge transfer, preservation, and commercialization of herbal products. Through case studies and empirical data, the paper highlights the significance of fostering a knowledge society that values and sustains indigenous wisdom, ultimately contributing to economic growth and sustainable development in Assam.